Ayutthayan Protective Practices and Devices: Manual of Wat Pradusongtham - Cholvijarn, Potprecha (Journal of International Buddhist Studies, 2026)
This article presents a summary and analysis of protective practices and devices described in an eighteenth-century manual from Wat Pradusongtham. This temple was an important meditation center during the late Ayutthaya period and the seat of a monk of a Rachakhana rank. The manual describes the legend and characteristics of the Triple Gem Qualities yantras which are three protective diagrams that represent the qualities of the Buddha, Dhamma, and Sangha, along with the Ratanamālā protective chant associated with them. It also provides instructions for visualizing four Pali syllables, na, ma, a, and u, which represent the four precious gems and the four elements (dhātu) that make up the body and the physical world. These four gems are used by the adept to manipulate the forces of nature, cure illnesses, perform miraculous powers, and activate protective devices.